Cognitive deficits of executive functions and decision‐making in obsessive‐compulsive disorder. Issue 5 (10th July 2013) - Dittrich, Winand H.; Johansen, Thomas
Abstract : The nature of cognitive deficits in obsessive‐compulsive disorder (OCD) is characterized by contradictory findings in terms of specific neuropsychological deficits. Selective impairments have been suggested to involve visuospatial memory, set shifting, decision‐making and response inhibition. The aim of this study was to investigate cognitive deficits in decision‐making and executive functioning in OCD. It was hypothesized that the OCD patients would be less accurate in their responses compared to the healthy controls in rational decision‐making on a version of the Cambridge gambling task (CGT) and on the color‐word interference test and on a version of the Tower of Hanoi test (tower test) of executive functioning. Thirteen participants with OCD were compared to a group of healthy controls (n = 13) matched for age, gender, education and verbal IQ. Results revealed significant differences between the OCD group and the healthy control group on quality of decision‐making on the CGT and for achievement score on the tower test. On these two tasks the OCD group performed worse than the healthy control group. The symptom‐dimension analysis revealed performance differences where safety checking patients were impaired on the tower test compared to contamination patients. Results are discussed in the framework of cognition and emotion processing and findings implicate that OCD models should address, specifically, the interaction between cognition and emotion. Here the emotional disruption hypothesis is forwarded to account for the dysfunctional behaviors in OCD. Further implications regarding methodological and inhibitory factors affecting cognitive information processing are highlighted.